Detection of clostridium difficile from an enhancement broth by gas-liquid chromatography - Hassan, H.; Cheng, S.C. (College of Pathologists, Academy of Medicine Malaysia, 1991)
Gas-Liquid cl~romatograpl~y (GLC) was used to detect tlle presence of isocaproic acid produced by Clostridium difficile from 54 stool san~ples grown in cycloserine-cefoxitin brotli. Isocaproic acid was detected in 12 samples of which 5 were confirmed to be Clostridium difficile by culture and biocllemical tests. Tlle detection of isocaproic acid by GLC together with the presence of presumptive colonies on primary selective culture media provides a more rapid laboratory diagnosis for Clostridium difficile.